PENGEMBANGAN INSTRUMEN UNTUK MENGUKUR KEMAMPUAN PERSEPSI VISUAL DAN KESADARAN LINGUISTIK SISWA SEKOLAH DASAR - Nabilah, Ayundha; Damaianti, Vismaia S; Agustin, Mubiar (Profesi Pendidikan Dasar, 2018)
Abstract: The aim of this paper is to describe the development and validation of test instrument that measure students’ visual perception and linguistic awareness. This is a part of a bigger study of quasi-experiment research which investigates the use of story reading through big book towards primary school students’ visual perception and linguistic awareness. The content validity is done by the expert judgment. Besides, items validity obtained from the trial tested to the first grader of primary schools. There are two sets of questions that consist of the same indicators but different question. 33 students fill set 1 and 30 students fill set 2. The result of expert validation is 87%, meanwhile, the item validity shows valid and invalid items. The researcher combined set 1 and set 2 to get the representation item from all indicators. The test reliability is in the good level. Based on these findings, the implication is that the instrument could be used due to its validity and reliability in measuring students' visual perception and linguistic awareness.